(untitled) (UNWE Yearbook, 2009)
The paper deals with a fundamental problem of the international economy under the conditions of globalization. The author argues an objective necessity for the global management of the international economic system, identifies the mission and the basic objectives of the global economic management. The paper reviews and critically discusses the main conceptual models of the global management of the international economic system and more specifically, focuses on the operating model of the neo-liberal institutionalism – namely, .the interpretation of its theoretical and conceptual basis, its historical evolution, its achievements and weaknesses. The analysis is linked to the current crisis processes of the international economic system. As a conclusion, it is argued that a profound reform of the institutionalized management model of the international economic system is required in order to match it against the requirements of the modern, highly globalized economy. Some alternative ideas for constructing the mechanism under review have been outlined.